Emergent online discourses and the (re)framing of women’s identity - Sibongile Mpofu (Communicare)
The advent of social media communication platforms, specifically blogs as sites of political engagement, means that they now constitute the key carriers of democratic public discourse. Previously marginalised groups such as women can now deliberate, interpret and re-frame their own narratives and identities. This article examines how Zimbabwean women are using blogs to resist and subvert women’s ascribed identities, improve the political, economic and cultural representations of women, and enhance women’s participation in politics. Using feminist critical theory, the article describes how women-owned content from selected Zimbabwean blogs frames women’s political, economic and cultural identities, and how women producing their own messages are improving women’s representation in society. Data obtained through qualitative content analysis of blog posts reveal that, as sites of agency, blogs offer possibilities for reframing and re-presenting women’s political and cultural identities. Blogs act as sites for the subversion of ascribed identities that continue to position women as second-class citizens. The article concludes that digital media, particularly blogs, can be used as sites of resistance to power by bringing to the fore counter narratives that have been obscured from mainstream discourse, and at the same time affording women direct influence over their public image.